Effects of CPO Biodiesel Blend Ratio on the Performance and Emission of Compression Ignition Engine - Md Noor, Muhamad Amirulhadi; Zulkifli, Abd Fathul Hakim (Progress in Engineering Application and Technology, 2020)
This study investigates the effect on performance and emission of various biodiesel blend which is 7% (B7), 15% (B15), and 30% (B30) by using crude palm oil as the feedstock and blending with diesel fuel. Parameters involve in this test are brake power, torque, and fuel consumption that is carried out by running 4-cylinder common rail CI engine of Toyota Hilux on a chassis dynamometer with different road speed which is 60, 90 and 110 km/h. SPTC any car auto check gas & smoke analyzer was used to determine gas emission such as HC, CO, CO2, O2, NOx, Lambda, and smoke opacity while ono sokki were used to measure fuel flow rate. The increase of the blending ratio has resulted in low emission for CO and NOx. Brake power increase but decreasing torque occurs at high road speed due to mechanical friction. The high viscosity of fuel increase the fuel consumption and decrease engine performance.